Pengkajian Agama secara Historis - Tarigan, Mardinal; Aprila, Gusti; Pratama, Riswanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As we know that history cannot be separated from a series of events limited by the space and time in which the events occurred. Many people say that history is something static that cannot be repeated based on its context. Along with the development of human knowledge and the potential for great curiosity, it has influenced people's perspectives on history, which used to consider history as static, rigid, and even without any contribution to the advancement of scientific studies. However, this view has been shaken by the struggle of Islamic studies, where history is always dynamic, following the